KODE SELF-DUAL SIKLIK ATAS RING RANTAI BERHINGGA - Juli Loisiana Butar-Butar (JURNAL CURERE, 2020)
The self-dual cyclic code is a cyclic code where its dual is the same as the cyclic code. This paper will discuss the necessary and sufficient conditions for the non-trivial existence a self-dual cyclic code over a finite chain ring. With this necessary and sufficient conditions, an algorithm is constructed about the construction of a self-dual cyclic code over a finite chain ring with length n. The polynomial factorization x^n-1 over finite field F_q is required in this algorithm steps. This is because each generator element of cyclic self-dual code over finite chain ring corresponds to an ideal from ring to ring F_q [x]/(x^n-1) which is a factorization from x^n-1 over finite field to F_q.